Comparing intracerebral hemorrhages associated with direct oral anticoagulants or warfarin. (27th March 2018) - Kurogi, Ryota; Nishimura, Kunihiro; Nakai, Michikazu; Kada, Akiko; Kamitani, Satoru; Nakagawara, Jyoji; Toyoda, Kazunori; Ogasawara, Kuniaki; Ono, Junichi; Shiokawa, Yoshiaki; Aruga, Toru; Miyachi, Shigeru; et al.
Abstract : Objectives: This cross-sectional survey explored the characteristics and outcomes of direct oral anticoagulant (DOAC)–associated nontraumatic intracerebral hemorrhages (ICHs) by analyzing a large nationwide Japanese discharge database. Methods: We analyzed data from 2, 245 patients who experienced ICHs while taking anticoagulants (DOAC: 227; warfarin: 2, 018) and were urgently hospitalized at 621 institutions in Japan between April 2010 and March 2015. We compared the DOAC- and warfarin-treated patients based on their backgrounds, ICH severities, antiplatelet therapies at admission, hematoma removal surgeries, reversal agents, mortality rates, and modified Rankin Scale scores at discharge. Results: DOAC-associated ICHs were less likely to cause moderately or severely impaired consciousness (DOAC-associated ICHs: 31.3%; warfarin-associated ICHs: 39.4%; p = 0.002) or require surgical removal (DOAC-associated ICHs: 5.3%; warfarin-associated ICHs: 9.9%; p = 0.024) in the univariate analysis. Propensity score analysis revealed that patients with DOAC-associated ICHs also exhibited lower mortality rates within 1 day (odds ratio [OR] 4.96, p = 0.005), within 7 days (OR 2.29, p = 0.037), and during hospitalization (OR 1.96, p = 0.039). Conclusions: This nationwide study revealed that DOAC-treated patients had less severe ICHs and lower mortality rates than did warfarin-treated patients, probably due to milder hemorrhages at admission and lower hematoma expansion frequencies.